The Influence of Artificial Body Fluids on Metallic Corrosion - Brett, Christopher M. A. (2002)
The influence of different artificial body fluids on metallic corrosion, all containing chloride ion, was investigated by measurements of open circuit potential, polarisation curves and electrochemical impedance on high speed steel, chosen owing to its high rate of corrosion. Two types of electrolyte fluid were studied, the first similar to saliva and the second to plasmatic serum and experiments were carried out over a period of immersion of 4h. Electrolytes similar to saliva were artificial saliva with and without lactic acid, and Glandosane that contains sorbitol and Na- carboxymethylcellulose organic components. Similar to plasmatic serum were phosphate buffer saline (PBS) and Krebs-Ringer solution. It was found that the organic components in the fluids partially block the metal surface and reduce the corrosion rate. From the results obtained, an approximate order of corrosion rate was established as: Artificial saliva ~ Glandosane ~ Krebs- Ringer solution < Artificial saliva without lactic acid ~ PBS. It is demonstrated that the equivalence of these different body fluids as bathing solutions should not be assumed.